Centralized Mobile Users Assignment Strategies for Energy Management in Het-LTE Networks - Barth, Dominique; Choutri, Amira; Kloul, Leila; Marce, Olivier (EAI Endorsed Transactions on Energy Web, 2016)
Power consumption control paradigm constitutes an incentive solution for the serious energy issues faced by operators. In this work, we investigate two mobile users assignment strategies for energy management in heterogeneous LTE networks. Both strategies are based on greedy algorithms which are of low complexity and allow on-line approaches suitable for femtocells management issue. Moreover, as the femtocells can be switched off and the macrocells have to remain always on, both strategies aim at selecting the femtocells to deactivate. That is, the mobile user may be moved from a femtocell to a macrocell or the other way around. The move is legitimate if the power consumption is lower and only if the QoS of the user is not sacrificed. Using simulation and real network data, we assess the performances of proposed strategies, in terms of energy consumption and efficiency of the network, the percentage of served mobile users, the real allocated capacity and the number of deactivated femtocells.
Keywords: heterogeneous lte network; energy consumption optimization; mobile users assignment strategies